RESEARCH MAPPING OF MACROECONOMIC INDICATORS: VOSVIEWER BIBLIOMETRIC STUDY AND LITERATURE REVIEW - Dewi, Nindi Dwi Tetria; Julaihah, Umi; Suprayitno, Eko; Budianto, Eka Wahyu Hestya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to determine the development of research regarding to Macroeconomic variables. The research was conducted from 1997 to 2022, by searching national and international journals indexed by Google Scholar, Sinta, and Scopus via the Perish/Harzing application, with the keyword “Macroeconomics”. Based on the search results, there were 441 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications had increased significantly every year. Furthermore, based on the results detected using the VOSviewer application, research related to influence of Macroeconomic variables is divided into 5 clusters and 139 items. Meanwhile, based on the results of a literature review study, there are 2 main themes related to influence of Macroeconomic variables. The implication and contribution of this research is to map topics that are often researched by researchers, so that they can be a referen.